Demystifying Artificial Intelligence (AI) for Early Childhood and Elementary Education: A Case Study of Perceptions of AI of State of Missouri Educators - Arnone, K.; Hutson, J.; Woodruff, K. (INTI International University, 2023)
Artificial intelligence (AI) and its impact on society have received a great deal of attention in the past five years since the first Stanford AI100 report. AI already globally impacts individuals in critical and personal ways, and many industries will continue to experience disruptions as the full algorithmic effects are understood. However, with regard to education, adopting in disciplines remains limited largely to Computer Science and Information Technology in postsecondary education. Recent advances with technology are especially promising for their potential to create and scale personalized learning for students, to optimize strategies for learning outcomes, and to increase access to a more diverse population. Research has confirmed that the current use of AI in education (AIEd) leads to positive outcomes, including improved learning outcomes for students, along with increased access, increased retention, lower cost of education, and decreased time to completion. Future uses of AI will include the following: enabling engaging and interactive education anytime and anywhere; personalized AI mentors that will help students identify and reach their goals; and mass-personalization that will allow AI to be tailored to each student’s learning style, level, and needs. Yet with all the potential benefits that AI and machine learning (ML) may provide students, there remains a general reticence to adopt this technology because of misconceptions and perceptions that elementary educators will need expensive equipment, robust support from IT, or to retool and learn programming or coding. As such, this study seeks to identify current perceptions early childhood, and elementary educators in the state of Missouri, USA have towards AI in general; the policies, training and existing resources in districts regarding technology in general and AI in particular; relative comfort with technology and willingness of educators to adopt new technologies for classroom instruction; and perform a needs assessment for necessary infrastructure, including reliable internet access, hardware and software. Results indicate a broad acceptance and willingness to adopt AI in daily activities and classroom instruction, but barriers to entry were identified as lack of resources and training.